Punctuation in English & Portuguese Translations: When Every Point Counts - de Ataide Melo, Cecil (Meta)

(untitled) (Les Presses de l'Université de Montréal, 1990)
AbstractThis is an investigate study on the frequency of punctuation use in Brazilian Portuguese and American English translations. Six textual pairs were selected, each representing a particular genre of translation. Punctuation was divided into two contrasting categories. Under terminal punctuation were placed marks which came at the end of sentences and caused the next word to be capitalized. Under internal punctuation were included marks which appeared within the sentence limits. 1692 marks in 622 sentences were carefully tabulated and constituted the corpus of this project. Results indicated that Portuguese texts were considerably more populated by various punctuation marks than their English counterparts. Frequent rhetorical pauses, tolerance towards longer and more complex sentences, and occasional use of double punctuation invited a higher ratio of marks per sentece in the Portuguese texts. In the last part of the paper, a number of conventions governing punctuation usage in the two languages are discussed, providing a direct application to the training of translators and students of foreign language composition and rhetoric.